Secondary Education Students’ Perceptions, Enjoyment, and Satisfaction in Using Mobile Devices for English Learning (Lectio: Journal of Language and Language Teaching, 2025)
This study investigates secondary school students’ perceptions, enjoyment, and satisfaction in using mobile devices for English learning. Employing a survey design, the research involved 100 students (48 male, 52 female) who completed a structured questionnaire distributed via Google Forms. Data were analyzed using interval-level interpretation based on Pimentel’s (2010) scale. The findings reveal that students perceive mobile devices as highly usable, engaging, and motivating, with perception, interest, and enjoyment rated in the very high category and satisfaction rated high. Ease of use emerged as the most significant factor influencing positive attitudes, while enjoyment and interest contributed to sustained engagement and autonomous learning. The study highlights the practical implications of integrating mobile devices into structured, goal-oriented learning activities that balance interactivity, accessibility, and pedagogical guidance. Despite its contributions, the research is limited to a single school and relies on self-reported measures, which may affect generalizability. Future studies are recommended to employ longitudinal designs, compare different school contexts, or examine the impact of specific applications on language learning outcomes. Overall, this study provides empirical evidence that mobile-assisted learning is an effective, flexible, and motivating tool for enhancing English proficiency among secondary school students, offering both cognitive and affective benefits when thoughtfully implemented.